Factors associated with deterioration of myocardial inotropic function in patients with coronary artery disease - O. A. Osipova; R. N. Shepel; N. M. Agarkov; E. V. Gosteva; V. V. Demko; A. A. Kuzub; A. S. Brizhaneva (Кардиоваскулярная терапия и профилактика)
Material and methods. One hundred patients with functional class III-IV CAD, stage I-IIa heart failure with LV ejection fraction (EF) >40%, successful coronary artery bypass grafting, SYNTAX Score of 33. During hospitalization, echocardiography, matrix metalloproteinase 9 (MMP-9), tissue inhibitor of metalloproteinase 1 (TIMP-1), monocyte chemoattractant protein 1 (MCP-1) were studied, while systemic immune-inflammation index (SII) was estimated. After 6 months, echocardiography revealed a group of patients with a decrease in LVEF.Results. The following factors of decreased LVEF were identified: type 2 diabetes, chronic kidney disease (p<0,001), >4 comorbid diseases (r=-0,597, p<0,001), increase in SII by 44,6% (p<0,001), MMP-9 by 62% (p<0,001), MCP-1 by 55,1% (p<0,001), TIMP-1 by 45,8% (p<0,001). An inverse relationship was found between LVEF and the level of SII (r=-0,626, p<0,001), MCP-1 (r=-0,747, p<0,001), MMP-9 (r=-0,718, p<0,001). There were following threshold values for predicting a decrease in LVEF: SII — 356,43, MMP-9 — 318,7 ng/ml, MCP-1 — 459,6 pg/ml.Conclusion. There are following markers of decreased LVEF in patients with CAD 6 months after successful coronary artery bypass surgery: type 2 diabetes, chronic kidney disease, >4 comorbid diseases, SII, MMP-9 and MCP-1 with a threshold value of 356,43, 318,7 ng/ml and 459,6 pg/ml, respectively.